Differential gene expression in a subpopulation of Phaeodactylum tricornutum with enhanced growth and carotenoid production after FACS-mediated selection - Sean Macdonald Miller; Andrei Herdean; Vishal Gupta; Brandon Signal; Raffaela M. Abbriano; Peter J. Ralph; Mathieu Pernice (Journal of Applied Phycology, 2023)
Fluorescence-Activated Cell Sorting (FACS) is a powerful method with many applications in microalgal research, especially for screening and selection of cells with improved phenotypes. However, the technology requires review of gene expression changes responsible for enhanced phenotypes in sorted populations. Phaeodactylum tricornutum cells were sorted using FACS with excitation/emission parameters targeted to favouring the industrially-relevant carotenoid fucoxanthin. The resulting cultures showed significantly higher growth rate (1.10 ×), biomass (1.30 ×), chlorophyll a levels (1.22 ×) and fucoxanthin content (1.28 ×) relative to the wild-type strain. RNA-seq was used to elucidate the underlying molecular-level regulatory changes associated with these traits and represents the first study do so on FACS-sorted microalgal cultures. Transcriptome analysis corroborated evidence of increased chlorophyll a and fucoxanthin, showing enrichment for the genes/pathways for tetrapyrrole biosynthesis and for suites of genes directly related to photosynthesis. Only three genes were upregulated in the MEP (non-mevalonate) pathway to carotenoid biosynthesis pathway, suggesting either a strong influence of IDI , CRTISO5 and ZEP1 on fucoxanthin biosynthesis or a post-transcriptional or post-translational mechanism for the observed increase in fucoxanthin content.